Koncepcja oceny kondycji finansowej przedsiębiorstwa na podstawie modelu wielokołowego - Kowalak, Robert (Financial Analysis of Corporate with Multiwheel Model, 2008)
The article presents the conception of wheeled model of the assessment of the financial position of an enterprise. This model is based on financial ratios and a surface schedule is demonstrating them on the wheel. For them the bigger surface area of the circle presents, the better financial condition. Theoretical deliberations are supported with empirical example of Budimex SA.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 44-51